2016
DOI: 10.1093/ntr/ntw105
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of the Association Between Exposure to Environmental Tobacco Smoke and Periodontitis Endpoints Among Nonsmokers

Abstract: Objective: A systematic review was conducted to summarize the epidemiological evidence on environmental tobacco smoke (ETS) exposure and prevalent periodontitis endpoints among nonsmokers. Methods: We searched PubMed, EMBASE, Web of Science, Pro-Quest dissertations, and conference proceedings of a dental research association. We included studies from which prevalence odds ratios (POR) could be extracted for periodontitis determined by examiner measurements of clinical attachment level (CAL) and/or probing pock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
(176 reference statements)
0
29
0
Order By: Relevance
“…Previous studies have indicated that smoking, which may suppress an innate immune response of periodontal tissue, is a major risk factor for periodontitis . Several in vitro studies have determined that smoking can affect the expression of AMPs in gingival epithelial cells or skin keratinocytes (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that smoking, which may suppress an innate immune response of periodontal tissue, is a major risk factor for periodontitis . Several in vitro studies have determined that smoking can affect the expression of AMPs in gingival epithelial cells or skin keratinocytes (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that smoking, which may suppress an innate immune response of periodontal tissue, is a major risk factor for periodontitis. [16][17][18] Several in vitro studies [19][20][21][22] have determined that smoking can affect the expression of AMPs in gingival epithelial cells or skin keratinocytes (Table 1). Besides, some cross-sectional, in vivo studies [23][24][25] have sought to identify the effect of smoking or nicotine use on AMP expression in saliva or gingival crevicular fluid of periodontitis patients ( Table 1) HGECs -HBD-2: (i) experimental group with cigarette exposed for 15 or 30 min>non-exposed group (control group) (P<.05); (ii) experimental group with cigarette exposed after 24 h>non-exposed group (control group) (P<.01); (iii) experimental group with cigarette exposed after 30 min>experimental group with cigarette exposed after 15 min (P<.05); HBD-3: (i) experimental group with cigarette exposed after 3 h>nonexposed group (control group) (P<.01); (ii) experimental group with cigarette exposed after 30 min>experimental group with cigarette exposed after 15 min (P<.01) HNP, produced by neutrophils, are very abundant in tissue and secretions of the oral cavity.…”
Section: Relationship Between Antimicrobial Peptides Periodontal Dmentioning
confidence: 99%
“…Tobacco use has been associated with increased disease progression and severity, as well as with refractory disease . Risk appears dose‐related while environmental smoke exposure may also be associated with increased risk of destructive forms of periodontitis . At the population level, smoking alone may account for most cases of periodontitis in adults in developed nations .…”
Section: Periodontal Diseases and Cigarette Smokingmentioning
confidence: 99%
“…3,4 Risk appears dose-related 1,5,6 while environmental smoke exposure may also be associated with increased risk of destructive forms of periodontitis. [7][8][9] At the population level, smoking alone may account for most cases of periodontitis in adults in developed nations. [10][11][12][13] Indeed, smoking rates and sales each predict periodontitis prevalence.…”
Section: Peri Odontal D Is E a S E S And Cig Are T Te S Mokingmentioning
confidence: 99%
“…6 Considering that periodontitis is more prevalent in elderly individuals and in view of worldwide (especially in developed countries) trend of population aging, an increase of periodontitis prevalence is expected in the near future. 6,7 Based on the fact that tobacco smoke is a well-known risk factor to periodontitis-mainly due to decrease of oxygenation though the vasoconstriction of tissues caused by the nicotine 8 -recent studies have shown that there is also biological plausibility for a possible relationship between periodontal disease and Cannabis use. [9][10][11][12][13][14][15][16] A longitudinal study carried in a birth-cohort in New Zealand showed that Recent studies have shown that there is also biological plausibility for a possible relationship between periodontal disease and Cannabis use, thus the aim of this study was to investigate whether the use of Cannabis is associated with periodontitis.…”
Section: Introductionmentioning
confidence: 99%